EPISTEMOLOGI HUKUM ISLAM PERSPEKTIF KEBUDAYAAN DOMINAN DI INDONESIA - Tanuri, Tanuri (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to explore the epistemology of Islamic law in the perspective of dominant culture, focusing on the boundaries of compromise between the basic principles of Sharia and local culture in the application of Islamic law. The background of this research is the fact that Muslim communities spread across different regions of Indonesia often have strong local traditions, which naturally influence their religious practices, including the application of Islamic law. This study examines the extent to which local traditions can influence the application of Sharia without undermining the essence of Islamic teachings, as well as how the boundaries accepted in such compromises are defined by Islamic scholars and practitioners. In relation to the dominant culture theory by Jerome Bruner, this study tries to understand how the dominant culture in a community can affect the meaning of Islamic law. Bruner stated that dominant culture shapes the perspective and behavior of individuals in a community, so in the context of Islamic law, there is a need to find a balance between the universal principles of Sharia and the need for local adaptation.